Modern Interpretation of Periodic Phenomenon - G. N. Fadeev; Yu. A. Lebedev; N. N. Dvulichanskaya (Высшее образование в России)
The presented work is devoted to the analysis of the modern stage of development of the theory periodic properties of chemical elements as a fundamental aspect of scientific worldpicture. Studying of the phenomenon of periodic properties of chemical elements has gone far beyond chemistry. It should be taken into account that even today, after the creation of two quantum theories of the electronic structure of the atom, after a century of experience in the study of chemical elements and the experimental discovery of antihydrogen, this problem is far from being exhausted. The generalization of theoretical and experimental studies of the quantum-mechanical aspects of the chemical properties of matter, the first results of the study of antimatter made it possible to set a hypothesis of the existence of a new fundamental characteristic of chemical element and to formulate the Periodic Law adequately – in keeping with modern concepts.